The right to refuse medical treatment and passive euthanasia - Đurđević, Tijana (Glasnik Advokatske komore Vojvodine, 2020)
Having in mind the obligation of a physician, stipulated in The Law on Patients' Rights, to respect the will of the patient even when the will is directed to the refusal of life-sustaining medical treatment, as well as the misdemeanor responsibility of a physician, prescribed by the same law, for treatment without the informed consent, the paper considers how the patient's right to refuse medical treatment affects the physician’s responsibility for the patient’s death in terms of the provisions of The Criminal Code. Also, the paper analyzes whether the physician is even able, in certain situations, to comply with provisions of the both mentioned regulations or whether the harmonization of legal solutions is needed.
Keywords: refusing medical treatment; passive euthanasia; informed consent; medical law; criminal law